Operational Strategy for Mobile Banking in India - Manjunath, Gowtham (2010)
Mobile banking (m-banking) business concepts have become ‘talk of the town’ these days. There has been considerable development in this field and what m-banking concept can offer. M-Rupee has developed a business model and plan to establish a mobile banking business in India taking the opportunity of the new unexplored market. This report is constructed in conjunction with the business plan, which describes the formulation and broader aspects of M-Rupee operational strategy. To understand the operations strategy of the business, a brief overview of the business is presented. M-Rupee is designed to work on business correspondent or agent network based mobile banking. All the M-Rupee transactions are carried out through ‘M-Rupee mobile application’, which is installed on agents’ and customers’ phones. For M-Rupee services like cash withdrawals and deposits, the customer interacts with the agent to transact, whereas for services like bill payments and remittance, customers can directly carryout transactions using the mobile application. All the transactions will be linked to customer’s banks account, so it is mandatory to have a bank account use M-Rupee services. The business will be built as a joint venture with a bank, and they will be an integral part of the business, which is also a mandate according to the RBI (Reserve Bank of India) M-banking norms. The various mobile banking models such as bank focused, bank-led and nonbank-led are discussed to understand the operational differences. The general stakeholders’ analysis and their expectations are gathered and the ones which are important to the M-Rupee are highlighted and analysed. The Operational model explains the functioning and interactions among the business entities such as customers, the agent network, M-Rupee and the bank. The end-to-end value chain of M-Rupee is designed to show the value creation at various levels of the business stream. The technical overview analyses the technical functionality requirements of the business showing the various system options under - mobile application systems, the gateway server, core bank systems, their communication model and the operational differences. The retail agent network models are analysed to counter the underlying risks involved in business correspondent form of m-banking systems. Some of the best practices are selected and adapted for modelling M-Rupee agent selection and setup process.